Moral Threshold Model is Universal? Initial Evidence from China’s Collectivist Culture - Xiao W (Dove Medical Press, 2021)
Weilong Xiao1,2 *, Binghai Sun1 *, Hui Zhou,3 Liting Fan,1,2 Changkang Sun,1 Yanhong Shao4 1College of Teacher Education, Zhejiang Normal University, Jinhua, Zhejiang, People’s Republic of China; 2Key Laboratory of Intelligent Education Technology and Application of Zhejiang Province, Zhejiang Normal University, Jinhua, Zhejiang, People’s Republic of China; 3Jinhua Advanced Research Institute, Jinhua, Zhejiang, People’s Republic of China; 4Zhejiang International Studies University, Hangzhou, Zhejiang, People’s Republic of China* These authors contributed equally to this workCorrespondence: Changkang SunCollege of Teacher Education, Zhejiang Normal University, 688 Yingbin Road, Jinhua, 321004, Zhejiang, People’s Republic of ChinaEmail 1158067980@qq.comYanhong ShaoZhejiang International Studies University, 299 Liuhe Road, Xihu District, Hangzhou, 310013, Zhejiang Province, People’s Republic of ChinaEmail yhshao2003@126.comPurpose: People choose actions that maintain their moral self-regard. This paper explains how one’s moral actions influence moral self-regard. The moral threshold model (MTM) has been proposed by scholars and tested using a limited sample. However, whether the MTM is universally applicable among people is still unknown.Participants and Methods: Our sample comprised 1761 individuals living in China, a collectivist culture, who were recruited to test the two main hypotheses of the MTM. Participants engaged in a hypothetical investment task.Results: 1) When the beneficiary was a prosocial cause, participants showed stronger preferences for smaller guaranteed positive payouts over larger uncertain ones; 2) as compared to making decisions for charities, when a participant made decisions exclusively for themselves, the maximum potential benefit was more likely to influence participant behavior.Conclusion: The current study provides initial evidence for the validity of using the worst outcome avoidance (WOA) hypothesis of MTM among members of China’s collectivist culture, indicating that the WOA hypothesis of MTM may have universal application.Keywords: collectivist culture, morality, moral self-regard, prosocial behavior, egoistic behavior